"Blessing gud ine " the lived experience of elderly celibate priests. - Rongcales, Natalio M. (Natalio M. Rongcales, 2018)
This study explored the lived experiences of elderly celibate priests (60 years old and above) and how it influenced their self-concept. Unstructured-interview was used to gather the data from 6 Waray elderly clerics. Interpretative Phenomenological Analysis (IPA) was used to interpret the lived experience of elderly priests because it is beneficial in discovering the hidden meaning of the participants' self-concept. Results showed that the self-concept of elderly celibate clerics has 3 main components: mind, body, and society. Our interpretation revealed that the lived experience celibacy of elderly clerics enhanced their self-concept because it gave them a sense of achievement after hurdling many struggles and eases with their lengthy practice. Strategies in managing their self-concept include reframing, legitimizing their practice, and social support system. Theoretical and practical implications are discussed on how the Church officials and families should support the practice of celibacy.